2021
DOI: 10.1093/jue/juab027
|View full text |Cite
|
Sign up to set email alerts
|

Rats and the COVID-19 pandemic: considering the influence of social distancing on a global commensal pest

Abstract: Rats contaminate foods and spread pathogens. Thus, changes in rat populations have consequences for society, especially in densely-populated cities. Following widespread social distancing and lockdown measures to curtail SARS-CoV-2, worldwide media outlets reported increased sightings of rats. To document possible changes in rat populations, we: (i) examined public service requests in the 6 years before, and during, ‘lockdown’ in New York City; (ii) used spatial analyses to identify calls in proximity to food … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Landfills have been proven to unintentionally provide food for generalist and synanthropic species that can be excellent reservoirs of zoonotic pathogens PLOS ONE [91], which may explain the case of M. musculus in SON. Consistently, two studies have found an increase in the movement and abundance of commensal rodents following the onset of the COVID-19 lockdown in New York [92] and Sydney [93]. These changes may potentially promote the spread of pathogens transmitted by M. musculus, R. rattus, and other invasive rodents.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Landfills have been proven to unintentionally provide food for generalist and synanthropic species that can be excellent reservoirs of zoonotic pathogens PLOS ONE [91], which may explain the case of M. musculus in SON. Consistently, two studies have found an increase in the movement and abundance of commensal rodents following the onset of the COVID-19 lockdown in New York [92] and Sydney [93]. These changes may potentially promote the spread of pathogens transmitted by M. musculus, R. rattus, and other invasive rodents.…”
Section: Discussionmentioning
confidence: 63%
“…musculus in SON. Consistently, two studies have found an increase in the movement and abundance of commensal rodents following the onset of the COVID-19 lockdown in New York [ 92 ] and Sydney [ 93 ]. These changes may potentially promote the spread of pathogens transmitted by M .…”
Section: Discussionmentioning
confidence: 64%
“…A temporary version of such a scenario was mimicked during the early days of the pandemic when major cities were quarantined, restaurants were closed down and patterns of food waste availability were dramatically altered. During this interval, rat populations appear to have needed to seek out alternate food sources and moved from commercial to residential areas (Parsons et al, 2021). In an urban future in which waste is greatly reduced, one wonders, would rats and pigeons still persist in cities?…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 was present in Switzerland from early 2020 and from late February 2020 public gatherings were increasingly restricted, leading to a dramatic shift in the places where people spent their time. The pandemic appears to have made some pests, such as Rodentia, Zygentoma, S. paniceum and Columbidae more apparent, as a part of the changing observations of urban fauna [19,[30][31][32]. The year 2020 saw the largest ever number of records (2369) in the UPAS database, compared with the year before (2019: 2267) and after (2021: 1922).…”
Section: Covid-19 Effectsmentioning
confidence: 99%